2015
DOI: 10.1093/hmg/ddv120
|View full text |Cite
|
Sign up to set email alerts
|

Functional disruption of the dystrophin gene in rhesus monkey using CRISPR/Cas9

Abstract: CRISPR/Cas9 has been used to genetically modify genomes in a variety of species, including non-human primates. Unfortunately, this new technology does cause mosaic mutations, and we do not yet know whether such mutations can functionally disrupt the targeted gene or cause the pathology seen in human disease. Addressing these issues is necessary if we are to generate large animal models of human diseases using CRISPR/Cas9. Here we used CRISPR/Cas9 to target the monkey dystrophin gene to create mutations that le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(155 citation statements)
references
References 28 publications
1
153
0
1
Order By: Relevance
“…[16][17][18] Recent reports have indicated that the CRISPR/Cas9 system can be used for genetic modification in NHPs; however, this approach has not yet been applied to insert genes of interest into the AAVS1 safe harbor in NHP PSCs. [19][20][21] We have identified a CRISPR/Cas9 target sequence in the rhesus macaque PPP1R12C gene, generated safe harbor-targeted rhesus macaque iPSC (RhiPSC) lines with two relevant marker genes, and documented the stability of expression both in iPSCs and after differentiation to tissues of interest. Genes encoding human truncated CD19 (hDCD19) or GFP were chosen as reporters.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Recent reports have indicated that the CRISPR/Cas9 system can be used for genetic modification in NHPs; however, this approach has not yet been applied to insert genes of interest into the AAVS1 safe harbor in NHP PSCs. [19][20][21] We have identified a CRISPR/Cas9 target sequence in the rhesus macaque PPP1R12C gene, generated safe harbor-targeted rhesus macaque iPSC (RhiPSC) lines with two relevant marker genes, and documented the stability of expression both in iPSCs and after differentiation to tissues of interest. Genes encoding human truncated CD19 (hDCD19) or GFP were chosen as reporters.…”
Section: Introductionmentioning
confidence: 99%
“…However, HDR rates can be increased in some cell types through cell cycle synchronization 40 or the use of small molecules or proteins that interfere with alternate DNA-repair pathways 44,45 . In sum, Cas9-based technological advances have dramatically simplified the creation of modified vertebrate cell lines and animal models for the investigation of gene function during development and disease progression 25,38,[46][47][48][49][50][51][52][53][54][55][56] . A similar revolution is being realized by the use of nuclease-dead Cas9 (dCas9) to deliver effector domains to perturb gene expression and chromatin-modification states 57 .…”
mentioning
confidence: 99%
“…The modified Cas9n was found to have similar cleavage efficiency when two gRNAs were used, one targeted on each strand of the DNA, resulting in a double strand break. The technique has been widely adopted to create disease-modeling cell lines, rodent and non-human primate models and in non-viable human embryos (Liang et al 2015;Chen et al 2015). What has made the CRISPR system so accessible is that, unlike the zinc fingers and TALEs, the same core protein, Cas9, is used to target any sequence, whereas the targeting portion of the CRISPR system, the gRNA, is what varies.…”
Section: Gene Editing Enzymesmentioning
confidence: 99%